Thickness, morphology, and optoelectronic characteristics of pristine and surfactant-modified DNA thin films. (19th September 2017) - Arasu, Velu; Reddy Dugasani, Sreekantha; Son, Junyoung; Gnapareddy, Bramaramba; Jeon, Sohee; Jeong, Jun-Ho; Ha Park, Sung
Abstract: Although the preparation of DNA thin films with well-defined thicknesses controlled by simple physical parameters is crucial for constructing efficient, stable, and reliable DNA-based optoelectronic devices and sensors, it has not been comprehensively studied yet. Here, we construct DNA and surfactant-modified DNA thin films by drop-casting and spin-coating techniques. The DNA thin films formed with different control parameters, such as drop-volume and spin-speed at given DNA concentrations, exhibit characteristic thickness, surface roughness, surface potential, and absorbance, which are measured by a field emission scanning electron microscope, a surface profilometer, an ellipsometer, an atomic force microscope, a Kelvin probe force microscope, and an UV–visible spectroscope. From the observations, we realized that thickness significantly affects the physical properties of DNA thin films. This comprehensive study of thickness-dependent characteristics of DNA and surfactant-modified DNA thin films provides insight into the choice of fabrication techniques in order for the DNA thin films to have desired physical characteristics in further applications, such as optoelectronic devices and sensors.